PENGARUH PRAKTIKUM KIMIA HIJAU PADA SIKAP SISWA TERHADAP KIMIA - I Wayan Redhana; I Nyoman Suardana; I Nyoman Selamat; Luh Maharani Merta (EDUSAINS, 2020)
THE EFFECT OF GREEN CHEMISTRY LAB EXPERIMENTS ON STUDENTS' ATTITUDES TOWARDS CHEMISTRYAbstractThis study aimed to investigate the effect of green chemistry lab experiments and the traditional chemistry lab experiments on students’ attitudes towards chemistry. This type of study was a quasi-experiment with a non-equivalent pretest-posttest control group design. The population of this study was all the Class XI of Natural Sciences in SMA Negeri 4 Singaraja, totaling five classes. Samples were selected by a purposive sampling technique. Sciences of 2 and 5 was the control group taught by traditional chemistry lab experiments, while Class XI of Natural Sciences of 3 and 4 was the experimental group taught by green chemistry lab experiments. Students’ attitudes towards chemistry were measured by a questionnaire given to students before and after the chemistry lab experiments. The results of this study indicated that students’ attitudes toward chemistry were better in the green chemistry lab experiments with a mean score of 4.34 than in the traditional chemistry lab experiments with a mean score of 4.15. AbstrakPenelitian ini bertujuan menyelidiki pengaruh praktikum kimia hijau dan praktikum kimia tradisional pada sikap siswa terhadap kimia. Jenis penelitian adalah eksperimen kuasi dengan rancangan non-equivalent pretest-posttest control group. Populasi penelitian ini adalah seluruh siswa Kelas XI IPA di SMA Negeri 4 Singaraja yang berjumlah lima kelas. Sampel dipilih dengan teknik purpossive sampling. Kelas XI IPA 2 dan 5 sebagai kelompok kontrol yang diajar dengan praktikum kimia tradisional, sedangkan Kelas XI IPA 3 dan 4 sebagai kelompok eksperimen yang diajar dengan praktikum kimia hijau. Sikap siswa terhadap kimia diukur dengan inventori yang diberikan kepada siswa sebelum dan setelah kegiatan praktikum kimia. Hasil penelitian ini menunjukkan sikap siswa terhadap kimia lebih baik pada praktikum kimia hijau dengan skor rata-rata 4,34 dibandingkan dengan praktikum kimia tradisional skor rata-rata 4,15.